2013
DOI: 10.1017/s0033291713001116
|View full text |Cite
|
Sign up to set email alerts
|

Mood and anxiety disorders across the adult lifespan: a European perspective

Abstract: BackgroundThe World Mental Health Survey Initiative (WMHSI) has advanced our understanding of mental disorders by providing data suitable for analysis across many countries. However, these data have not yet been fully explored from a cross-national lifespan perspective. In particular, there is a shortage of research on the relationship between mood and anxiety disorders and age across countries. In this study we used multigroup methods to model the distribution of 12-month DSM-IV/CIDI mood and anxiety disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 59 publications
3
3
1
Order By: Relevance
“…The socio-demographic associations documented here are broadly consistent with previous studies in finding higher rates of both anxiety disorders and MDD among women (Parker and Brotchie, 2010; Altemus et al 2014) and the previously-married (Scott et al 2010; Leach et al 2013) along with less consistent inverse associations with age (de Graaf et al 2013; McDowell et al 2014). However, we are unaware of prior systematic efforts to examine nested associations in the way we did here.…”
Section: Discussionsupporting
confidence: 90%
“…The socio-demographic associations documented here are broadly consistent with previous studies in finding higher rates of both anxiety disorders and MDD among women (Parker and Brotchie, 2010; Altemus et al 2014) and the previously-married (Scott et al 2010; Leach et al 2013) along with less consistent inverse associations with age (de Graaf et al 2013; McDowell et al 2014). However, we are unaware of prior systematic efforts to examine nested associations in the way we did here.…”
Section: Discussionsupporting
confidence: 90%
“…We had identified the elderly as a priority group a priori because of their higher risks of social isolation, lack of digital connectivity and greater vulnerability to COVID-19. However, similar to other research that has consistently found declining prevalence of mental disorders with increasing age [45][46][47], in NZ older people appeared to be faring better than younger people. This is not to say older people were unscathed.…”
Section: Examination Of Vulnerable Groupssupporting
confidence: 86%
“…There is a substantial body of literature showing that adult inhabitants of urban areas are more likely to be diagnosed with a psychiatric disorder compared to those living in more rural areas [11,[15][16][17]. Retrospective studies showed that this increased risk for mental health problems may be even greater for those who grew up in a city [18], suggesting that the effects of an urban environment on mental health may be particularly influential during youth.…”
Section: Urbanicity and Mental Healthmentioning
confidence: 99%